Pembelajaran Mendengarkan Cerita “Ramayana” untuk Mengembangkan Pribadi Peserta Didik - Khoiruzzaim Kurniawan (Salimiya: Jurnal Studi Ilmu Keagamaan Islam, 2023)
This research aims to explore and analyze the impact of learning to listen to the story "Ramayana" on the personal development of Madrasah Ibtidaiyah (MI) Darussalam Pikatan students. Through this learning approach, this research evaluates the extent to which acceptance of the epic story "Ramayana" can contribute to the development of students' personal aspects, such as morality, ethical values, and increased cultural understanding. This research method involves an experimental research design with a control group and an experimental group. Data was collected through various assessment instruments involving observation, interviews and questionnaires. Data analysis was carried out quantitatively and qualitatively to understand changes that might occur in students' personalities after learning to listen to the story "Ramayana". It is hoped that the research results will provide an in-depth understanding of the learning potential of listening to epic stories as a tool for the personal development of students at MI level. The practical implications of these findings can provide guidance for developing curricula and learning approaches that are more effective in promoting cultural values ​​and character development in Islamic education environments.